Spectrum of Bloodstream Pathogens and Their Antimicrobial Susceptibility Patterns in a Tertiary Care Setting: A Retrospective Observational Study - Karmacharya, Abhishek; Pokhrel, Subrata; sharma, Damodar; Khadka, Chetan; Pradhan, Nickey; Phuyal, Navindra (Medical Journal of Eastern Nepal, 2026)
Background With a high mortality rate, bloodstream infections (BSI) are a serious worldwide public health burden. Delay in therapy has a significant impact on Patient’s outcomes, and rapid and precise pathogen diagnosis significantly improves patient care. Drug-resistant bacterial pathogens are a result of frequent inappropriate antibiotic usage and undiagnosed bloodstream infections. A lack of investigation on BSIs in Nepal has limited the understanding of their causes, prevention, and treatment.ObjectivesThe purpose of this study is to examine the bacteriological profile and antibiotic susceptibility of bloodstream infections in order to assess current trends.Methods This is a retrospective analysis of blood cultures from individuals suspected of having a bloodstream infection conducted at a hospital. We performed a retrospective examination of blood culture data from individuals suspected of having a bloodstream infection over a three-year period. Bloodstream infection, blood culture contamination, bacterial profile, and patterns of antibiotic resistance were all determined using data from the laboratory reports.ResultsA total of 544 isolates were isolated with Gram negative organisms being the most dominant. Acinetobacter spp. (20.6%), followed by Coagulase negative Staphylococci (CoNS) (17.28%), S. aureus (14.5%), and E. coli (9.4%) were the most significant bacteria. Excluding CoNS, the MDR rate among the remaining 447 isolates was 40.4%. K. pneumoniae had the greatest MDR burden (73.9%), then A. baumannii complex (58.3%) and S. aureus (46.8%). Overall, third-generation cephalosporin resistance was concerning, and glycopeptides and carbapenems are still effective against the majority of pathogens.ConclusionsThe presence of high-level multidrug resistant (MDR) Gram negative bacteria, especially Acinetobacter spp and K. pneumoniae, makes empirical treatment less effective. Our results suggest the need for local susceptibility-based approach and improved antibiotic stewardship in resource limited settings.